PECULIARITIES OF IMPROVING FUTURE TEACHERS’ EDUCATIONAL PROCESS IN THE SPIRIT OF PATRIOTISM - Kosbergenov Raxat Maxsetbaevich (Western European Studies, 2024)
The article describes the specific features and components of improving the process of educating future teachers in the spirit of patriotism by means of local historical materials. Also, the paper deals with the peculiarities of improving future teachers’ educational process in the spirit of patriotism taking into consideration the purpose of educational activities conducted in our country is aimed at forming a patriotic person who is able to show examples of self-sacrifice to develop the country
Keywords: spirituality; history; culture